Evidence of Differential HLA Class I-Mediated Viral Evolution in Functional and Accessory/Regulatory Genes of HIV-1 - Brumme, Zabrina L; Brumme, Chanson J; Heckerman, David; Korber, Bette T; Daniels, Marcus; Kadie, Carl; Bhattacharya, Tanmoy; Chui, Celia; Szinger, James; Mo, Theresa; Hogg, Robert S; Montaner, Julio S. G; et al. (PLoS Pathogens, 2007)
One of the greatest challenges facing HIV-1 vaccine design today is the formidable capacity of the virus for mutation and adaptation, a characteristic that has contributed to the extensive worldwide genetic variability of HIV-1 strains observed today. On an individual basis, evolutionary selective pressures imposed by each infected person's unique immune response results in the selection and outgrowth of viral "escape" mutants capable of evading immune recognition, while on a population basis, complex evolutionary selective pressures imposed by the highly polymorphic genes of the human immune system shape HIV-1 diversity on a global level. Making sense of the seemingly infinite complexity of HIV immune escape is of paramount importance in our goal of developing a successful HIV vaccine. The current study uses cutting-edge statistical methods to identify specific sites and patterns of human leukocyte antigen (HLA) class I-restricted escape mutations in various HIV genes. Researchers summarize their findings in the form of "immune escape maps," which highlight the differential contribution of immune imprinting to HIV genetic diversity, as well as identify specific sites in the viral genome under active immune selection pressure. Results from the present study contribute to our understanding of how human immune selective pressure contributes to variation in different HIV genes, and could help inform the development of HIV vaccines that take into consideration viral diversity.